Signal integrator function of CXXC5 in Cancer - Zihao An; Jiepu Wang; Chengzuo Li; Chao Tang (Cell Communication and Signaling)
Abstract CXXC type zinc finger protein 5 (CXXC5) is a member of the ZF-CXXC family and plays a pivotal role in signal integration and information transfer within cell signaling network. CXXC5 acts as a regulator in various physiological processes, and abnormalities in its protein structure or function have been linked to multiple pathological processes. In this article, we correspondingly describe the composition of the ZF-CXXC family, emphatically introducing the features of the CXXC5 gene and protein, review the role of CXXC5 in cellular signaling networks, the physiological and pathological processes associated with CXXC5 dysregulation, and particularly focus on the correlation between CXXC5 and cancers. Finally, we summarize the current therapies targeting CXXC5 and their potential applications, and discuss the intriguing findings from current studies, and the opportunities and challenges in future. Graphical Abstract